Keeping decentralisation in check: An exploration of the relationship between municipal audit outcomes and levels of service delivery in South African local government - Craig, Stephanie Ella (School of Economics, 2017)
In a decentralised system of governance, checks and balances are important to prevent corruption and ensure the optimal performance of public service organisations. However, such regulations need to strike a careful balance between not being too simple and avoiding onerous, unnecessary complexity. Furthermore, the devolution of responsibility cannot occur in isolation – it must be accompanied by financial and operational support. Although South Africa has always had some form of a decentralised governing system, the Constitution of 1996 has formally entrenched this into the country's current public administration. Local government, now a sphere within itself, is thus responsible for bringing the Bill of Human Rights to life, acting increasingly as the implementation arm for national government's policies and initiatives. Following the passing of the Local Government Municipal Financial Management Act of 2003 (MFMA), South African municipalities are also required to comply with rigorous, annual auditing regulations. Intended to enforce sound financial governance and prevent abuse of devolved power, the influence of the audits is widely expected to positively impact other areas of municipal operations, ensuring well-run public organisations able to fulfil their service delivery mandate. Indeed, the general public uphold clean audit outcomes – a standard unique to South African municipal audits – as the only acceptable result and indication of effective local governance. However, this is not always the case. By examining the extent to which financial compliance, as represented by municipal audit outcomes, relates to local government service delivery performance, this thesis investigates whether the auditing regulations are appropriately designed to achieve their intended outcomes and asks how much of an impact sound financial management has upon municipal operations. The results suggest that, whilst there does appear to be a weak, positive relationship between clean audits and service delivery in some instances, on the whole the audit outcomes are not strongly related to municipal operational performance. The capacity of local governments to deliver services appears to be far more a function of their operational context - particularly the regional wealth levels, population density, political influence and available infrastructure - than financial compliance and audit outcomes. Given the costs of the current auditing system and difficulties faced by municipal employees in relation to the regulations, this thesis concludes with recommendations for its adaptation. These include amending its current one-size-fits-all design and moving away from a compliance focus towards performance, value-based auditing. In addition, local municipalities should be provided with greater amounts of operational support, as financial regulations alone – even when optimally designed – cannot be relied upon to keep the performance of South Africa's decentralised system of governance in check.